Flow of knowledge in proof-of-concept activities : examining the problem of interpretation using hermeneutics - Neto, Antonio Jose Rodrigues (2021)
Background. Proof-of-Concept (PoC) is a common practice in several disciplines, and is used in organizations for different purposes, including exploring, producing and disseminating knowledge of new information technology products. Objectives. One intriguing question has motivated the present research: What is the mechanism supporting the flow of knowledge in the context of PoC? Methods. This research was based on direct researcher participation in multiple PoC activities working collaboratively with several PoC practitioners, totaling 30 months of immersion. The research method is ethnography involving observations, notes, semi-structured interviews, and participation in the PoC world. Results. After analyzing 459 data points through the lens of hermeneutics, the authors learned that the production and dissemination of knowledge in the context of PoC did not occur only at the end of the PoC activity. Instead, the flow of knowledge occurred in different learning circles (based on hermeneutic circles) as an intrinsic connection to the context. It is the knowledge of the context that allows PoC practitioners to comprehend the construction of the cycles of production and dissemination of knowledge in PoC activities.